ANALISIS TENTANG NILAI – NILAI KARAKTER SISWA YANG MENONTON TELEVISI DI SD N 012 SIMPANG KANAN T.P. 2013/2014 - Yakub, Elni Yakub Elni; Saam, Zulfan Saam Zulfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This study aimed toanalyze thecharactervaluesof studentswhowatch televisionviewsofthe symptomsfoundinthe rightSDNSimpang0122013-2014school yearmost studentsspeakdisrespectfultoa friend, anystudentwhohas alwaysdemonstratedthe style ofthe artistintelevision, there arestudentswhodemonstrate thescene-withhisaction scenes, there arestudentswhoover actingwhilestudying, there aresomestudents who are sleepy henstudying, there arestudents who take thewordsthatare notin accordancewith mannerslikeweveIpikirin, lebay, verystupidandmasbulo, inschoolthe student's responsibilityis very low. It canbe seenfrom thelazy to dopicketdutyclassanddo notdo their homework, there arestudentswhoviolatedisciplinein schoolattendance, for example,cametoo late. The formulationmasalah bagaimana idea ofthe character ofthe studentswhowatchTVinSDNegeri012Simpang Kanan, howthe value ofthe character ofthe studentswhowatchTVinSDNegeri012Simpang Kananditinjaubackgroundofthe parents: a.This type of workparents. b. The education levelof parents. The purposeof this studyto describethe value ofthe character ofthe studentswhowatchTVinSDNegeri012Simpang Kanan, todeterminethe value ofthe character ofthe studentswhowatchTVinSDNegeri012Simpang Kananditinjaubackgroundofthe parents : a.This type of workparents. b. The education levelof parents. Inthis study using63samplesat012SDNSimpang Kanan. Of the63samplesthatexistwith28statementconsistsoftwocategories : yeswitha score of1anddid not score0thenobtainedan idea ofthe value ofthe character ofthe studentswhowatch televisioninSDN012Simpang Kanan. Self-control (45.4%), discipline (52.4%), Responsible and honest (76%), hard work and tenacious (67.9%), to defend the truth (76.2%) and the courtesy and politeness (65.5%). Keywords: Values, Character, students